2012
DOI: 10.3846/16486897.2011.645826
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Ozone Penetration in a Grain Layer / Ozono Skverbties Grūdų Sluoksnyje Modeliavimas

Abstract: Studies of grain drying with ozone-air mixture were carried out to detect the ozone penetration patterns through the grain mound of various moisture content (14.6 ≤ w 0 ≤ 23.0%) at different ozone concentrations (500 ≤ C 0 ≤ 1250 ppb) in the supplied air. The ozone penetration through the grain layer depends on the initial ozone concentration in the supplied air, ozonation time, velocity of the supplied air, height of the grain mound, initial grain moisture content and mycobiotic contamination of grain surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…To sum up the results of two weeks' experiments, we can conclude that significant drying of grain has occurred in the first three layers from the bottom, whereas in the first layer the grain was significantly overdried. The reason for the high grain moisture in the upper layers is apparently insufficient ventilation air velocity in the grain layer (see the results of the previous measurements), or insufficient specific air consumption in m 3 per m 3 •h -1 -cubic meters of air per 1 m 3 of grain per hour. In our case this indicator is 350 m 3 per m 3 •h -1 , the optimum would be 500-550 [10].…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…To sum up the results of two weeks' experiments, we can conclude that significant drying of grain has occurred in the first three layers from the bottom, whereas in the first layer the grain was significantly overdried. The reason for the high grain moisture in the upper layers is apparently insufficient ventilation air velocity in the grain layer (see the results of the previous measurements), or insufficient specific air consumption in m 3 per m 3 •h -1 -cubic meters of air per 1 m 3 of grain per hour. In our case this indicator is 350 m 3 per m 3 •h -1 , the optimum would be 500-550 [10].…”
Section: Methodsmentioning
confidence: 90%
“…Experiments [2] were carried out in a 0.45 m high column with the ventilation length for up to an hour. The authors of publication [3] also carried out experiments in the laboratory with a few tens of kilograms of grain and a layer of grain up to 1.2 m thick. The author of publication [4], in turn, has worked with a grain layer up to 0.5 m thick, the ozone concentration 2.4-8.2 mg•m -3 , the initial humidity of grain 17-28 %; and he believes that the ozone addition to the ventilation air allows reducing the duration of ventilation by 10-20 %.…”
Section: Introductionmentioning
confidence: 99%
“…concluded that ozone penetration through the stored grains is inversely proportional to the bed thickness. Steponaviciene et al . found that ozone absorption was higher in upper layers of the grains column.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone is a relatively stable molecule at low temperature and high relative humidity conditions, and it is only at higher concentrations and higher temperatures that it rapidly decays to oxygen . Therefore a low concentration and a long exposure time is more practical, is easy to generate, leads to no significant changes in proximate composition of stored grain and is environmentally friendly . The problems in ozone application for insect control in stored grains are closely related to the grain bed thickness, moisture content, and selection of ozone concentration, exposure time, mycobiotic contamination of grain surface and concentration of ozone at the outlet …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the reduction of mycotoxin contamination cannot be explained by only one factor. The adsorption and penetration of ozone in the sample rely on intrinsic and extrinsic factors such as the characteristics of the sample, initial contamination, exposure time, gas flow rate, column height and moisture content STEPONAVIČIENĖ et al, 2012;.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%